Probiotic Bacillus amyloliquefaciens C-1 Improves Growth Performance, Stimulates GH/IGF-1, and Regulates the Gut Microbiota of Growth-Retarded Beef Calves - Du, Renjia; Jiao, Shengyin; Dai, Yue; An, Jianbo; Lv, Jia; Yan, Xiaoni; Wang, Juan; Han, Bei (Frontiers in Microbiology, 2018)
Growth retardation of calves is defined as a symptom of impaired growth and development, probably due to growth hormone disorder as well as natural and environmental factors in livestock. The growth-promoting effects of probiotics were determined in 50 growth-retarded growth calves. They were supplied with Bacillus amyloliquefaciens C-1 (Ba, 4×1010CFU/d, n=16), Bacillus subtilis (Bs, 4×1010CFU/d, n=18), and negative control (NC, n=16) for 30 days. Pre- and post-intervention, the growth performance (weight gain rate, feed intake and feed conversion rate) was analyzed, the serum GH, IGH-1 and immunoglobulin levels were assayed, and the fecal microbiota was detected. Calves in Ba and Bs groups demonstrated increased body weight gain, feed intake and GH/IGF-1 levels, as well as a more efficient feed conversion rate, compared with NC group (P<0.05). Additionally, the abundances of bacteria contributing to the production of energy and SCFAs (short chain fatty acids), including Proteobacteria, Rhodospirillaceae, Campylobacterales, and Butyricimonas were increased compared with NC group(P<0.05, FDR<0.1); and the suspected pathogens, which included Anaeroplasma and Acholeplasma were decreased (P<0.05, FDR<0.1) in both the Bs and Ba groups. Akkermansia, which is involved in the intestinal mucosal immune response, was increased in Bs group after intervention (P<0.05), but inhibited no obvious difference in Ba group. The increased bacterial genera in Ba group were Sphaerochaeta and Treponema (P<0.05, FDR<0.1). These results indicate that the probiotics B. amyloliquefaciens and B.subtlis exhibited similar therapeutic potential in terms of growth performance by regulating hormones, and improving the intestinal and rumen development in growth-retarded animals.